KAJIAN TEKNO EKONOMI LAYANAN DATA WAP DI OPERATOR GSM - Harwindiadi, Dedi
Abstrak : This thesis presents a techno-economics study of implementation WAP data service. The topic was chosen because data service in mobile communication like GSM system are a need for operators as provider to increase their income, inside customers that need data access through cellular network. This condition is considered as potential business that need some planning analysis carefully in the implementations. Study of WAP data service will explain about WAP itself, technical factors that influences WAP network planning in GSM operator that take some IM-3 cases and financial factors with technoeconomic parameters like NPV, IRR, PI and Payback Period, so can get a feasibility of business of the WAP data service. Base on the result of techno economy study , using preference IRR = 22,6 % and Payback Periods = 4 years, this feasibility study show that WAP data service in the GSM operator with IM-3 case is feasible. The following techno-economic parameters proves the conclusion : NPV = RP 83.182.638.652 > 0; IRR = 45 % > 19 %; PI = 3,8 > 1 ; PBP = 3 year 11 month < 4 year andROI=228%.